Double and Single Yolked Duck Eggs: Their Contents and Dimensions Compared and the Mechanical Stimulation Hypothesis for Albumen Secretion Is Supported - Salamon , Attila; Kent, John P. (International Journal of Poultry Science, 2013)
The external dimensions, weight and contents (yolk, albumen, shell) of Double Yolked (DY) and Single Yolked (SY) eggs of the duck (Anas platyrhynchos domesticus) were measured and compared. The yolks in DY eggs did not differ in weight (p = 0.144), although each double yolk was significantly lighter than the yolk of a SY egg (p<0.001). DY albumen weight was below that expected of a SY egg of comparable weight. However, DY eggs had 24.5% more albumen on the basis of SY yolk weight. In DY eggs, the yolk closer to the airspace (Yolk 1) was heavier in 62.5% of the eggs and heavier yolks are regarded as the first in the ovulation sequence. Thus, DY eggs were divided into two groups based on yolk weight. In Group A, Yolk 1 was heavier. In Group B, Yolk 2 was heavier. Significantly more albumen was found in Group B (Group A: 51.37% vs. Group B: 53.29% albumen; p = 0.031). This supports the mechanical stimulation hypothesis, with the larger Yolk 2 stimulating the secretion of additional albumen by the magnum wall. It is suggested that work with DY eggs could provide a useful non-invasive tool to examine the mechanisms underlying albumen secretion.